2010
DOI: 10.1002/jbmr.20
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of IGF-1 are sufficient to establish normal body size and skeletal properties even in the absence of tissue IGF-1

Abstract: Use of recombinant insulin-like growth factor 1 (IGF-1) as a treatment for primary IGF-1 deficiency in children has become increasingly common. When untreated, primary IGF-1 deficiency may lead to a range of metabolic disorders, including lipid abnormalities, insulin resistance, and decreased bone density. To date, results of this therapy are considered encouraging; however, our understanding of the role played by IGF-1 during development remains limited. Studies on long-term treatment with recombinant IGF-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
60
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 42 publications
12
60
0
5
Order By: Relevance
“…In agreement with previous reports, HIT mice with elevated serum IGF-I had increased body weight compared with control mice at 8 and 16 wk of age ( Fig. 1A) (17,19). Mammary gland weight of HIT mice, however, was less than that of wild-type control (LL) mice at 4 wk of age, but did not differ from LL mice at 8 and 16 wk of age (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous reports, HIT mice with elevated serum IGF-I had increased body weight compared with control mice at 8 and 16 wk of age ( Fig. 1A) (17,19). Mammary gland weight of HIT mice, however, was less than that of wild-type control (LL) mice at 4 wk of age, but did not differ from LL mice at 8 and 16 wk of age (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Liver-specific IGF-I transgene expression in HIT and KO-HIT mice led to threefold increase in serum IGF-I above control mice at 4, 8, and 16 wk of age, as previously reported (17,19). In agreement with previous reports, HIT mice with elevated serum IGF-I had increased body weight compared with control mice at 8 and 16 wk of age ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…It has been shown that the more protein produced by the IGF1 gene is contained in the blood, the larger the individual. Mice with a damaged IGF1 gene have been shown to attain a very small size, while humans with a deletion in this gene are born with a body length considerably below the norm [7]. The IGF1 gene has a substantial effect on the size of individuals in some breeds of pig [8], cattle [9], as well as in canids [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that autocrine and paracrine IGF-I appears crucial for early postnatal and pubertal development of cortical bone, while circulating IGF-I, responsible for the endocrine effect, is mainly important for growth after puberty. In autocrine and paracrine IGF-I deficient mice high levels of serum IGF-I can permit postpubertal "catch-up" growth [18][19][20].…”
Section: Introductionmentioning
confidence: 99%